2018
DOI: 10.22399/ijcesen.408231
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Radiation Protection and Shielding Properties of 16 Slice Computed Tomography (CT) Facilities

Abstract: One of the fundamental principles of radiation protection is distance factor. In CT facilities maximum dose occurs near gantry and dose rate is decreases by distance. To know the rate of reduction of the amount of dose that distance is very important for radiation protection procedure especially for apply criterias of International Commission on Radiological Protection (ICRP) on radiation protection. This technical study aimed to investigate the backscattered dose amount from 16 Slice CT devices for verificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…In another study in 2018, the radiation dose rate at a distance of 20 cm from the gantry was found to be 48.5 mSv / h [19]. In both studies, the radiation dose rate at different distances from the gantry was measured.…”
Section: Distancementioning
confidence: 97%
“…In another study in 2018, the radiation dose rate at a distance of 20 cm from the gantry was found to be 48.5 mSv / h [19]. In both studies, the radiation dose rate at different distances from the gantry was measured.…”
Section: Distancementioning
confidence: 97%
“…Thus besides other code it has been in a variety of studies in radiation fields [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In the present study, the FLUKA Monte Carlo Code is utilized to calculate the radiation shielding capacity of the HAP+ Fe2O3 samples [18,[40][41].…”
Section: Fluka Monte Carlo Code Environmentmentioning
confidence: 99%
“…BT [11]. 2018 yılında yapılan bir başka çalışmada, gantriden 20 cm uzaklıktaki radyasyon doz hızı ise 48.5 mSv/h olarak bulunmuştur [12]. Her iki çalışmada da, gantriden farklı uzaklıklardaki radyasyon doz hızları ölçülmüştür.…”
Section: Bulgular Ve Tartışmaunclassified